Comprehensive Analysis of the Role of Technology in Enhancing Emergency Medical Services - Alghufaynah , Abdullah Hussain A; Al Sharyah , Saleh Hadi A; Al Sharyah, Hadi Salem F; Alsallum , Abdullah Mohammed A; Al Amer , Nasser Mana H; Ozran, Hussein Yahya H; Almansour , Ali Hadi M; Alsallum , Mahdi Hadi M; Al-Yami , Ali Hussein M; Alruwaili , Salem Muzil R; Asiri , Ahmed Sarwi A; Asiri , Ali Mohammed A; et al. (Journal of Ecohumanism, 2024)
This paper aims to explore the effect of technology on EMS; this paper focuses on the role played by technology in boosting efficiency and accuracy as well as the results of the patients treated. Modern tools, the three key innovations of telemedicine, automated dispatch systems, and wearable health devices, have greatly transformed care delivery by EMS professionals. Telemedicine helps in providing consultation and guidance from a distance for first responders, excluding the refs in resource-deficit areas, and enhancing the decision for pre-hospital care. Automated dispatch systems utilize artificial intelligence and real-time data to determine the optimal paths to get an ambulance where needed most during emergencies. On the other hand, inspection permits constant surveillance of vital signs, the identification of life-threatening emergencies, and a flow into the protocols of EMS wearables. The research in this paper combines numerical data and narrative understanding, demonstrating the efficiency of these technologies in mitigating world EMS issues, including scarce resources, slow response, and variations in the treatment of patients. The study shows how these innovations enhance operations and help avoid death by analyzing case lessons and using statistics. Also, it identifies the issues of high cost and professional training requirements, as well as the issue of data security. In summary, the paper focuses on how technology plays a central role in EMS and how it can help bring consistency in EMS between different care organizations.